ANALISIS INDEKS KEKERINGAN METEOROLOGIS MENGGUNAKAN METODE STANDARDIZED PRECIPITATION INDEX DI KABUPATEN PELALAWAN - Yogi Guntara; Sigit Sutikno; Lita Darmayanti (LPPM Universitas Abdurrab, 2023)
Drought is one of the natural phenomena indicated by the limited availability of water above, on the surface and in the ground. Pelalawan District has a history of drought which occurred in 2015 and resulted in a water crisis. Drought index measurement with the help of spatial techniques is often the key in assisting monitoring to determine drought prevention measures. This study conducted a spatial analysis to determine the distribution of drought using the Standardized Precipitation Index (SPI) method a 3-month time scales. This research used monthly satellite rainfall from 2010-2019. The results of the analysis show that extreme drought conditions occurred in June 2015 in Kuala Kampar sub-district with a value of -3.70.